2009
DOI: 10.1111/j.1399-3038.2008.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index in Belgian schoolchildren and its relationship with sensitization and allergic symptoms

Abstract: Results of studies of the influence of body mass index (BMI) on the allergic status are controversial. As a part of the Aalst Allergy Study, we assessed the prevalence of the different BMI categories (underweight, normal weight, overweight, and obesity) and a possible association between BMI and atopy in 1576 unselected Belgian schoolchildren, aged from 3.4 to 14.8 yr. BMI was used to determine weight status. Skin prick testing with the most common aeroallergens was performed. A parental questionnaire document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
41
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 41 publications
(56 reference statements)
8
41
2
3
Order By: Relevance
“…If one assumes that those without a history of allergy are less likely to have allergic asthma, Chen's observations suggest that obesity has a stronger relationship with non-allergic than allergic asthma. On the other hand, we have the results of several research groups that indicate a significant association between obesity and atopic sensitization (1,13,24) . It seems that the mechanisms for atopic sensitization associated with obesity need to be explored, and further cross-sectional studies are required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If one assumes that those without a history of allergy are less likely to have allergic asthma, Chen's observations suggest that obesity has a stronger relationship with non-allergic than allergic asthma. On the other hand, we have the results of several research groups that indicate a significant association between obesity and atopic sensitization (1,13,24) . It seems that the mechanisms for atopic sensitization associated with obesity need to be explored, and further cross-sectional studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…Some data showed a relationship of obesity and asthma only in females. Among a number of studies that have been conducted among children and adults, some have demonstrated an increased risk of atopy among overweight or obese individuals (11,12) , while others have found no association between adiposity and atopy (13,14) .…”
mentioning
confidence: 99%
“…The results from previous studies on BMI and allergic sensitization are inconclusive. Some studies showed an increased risk of sensitization, [19][20][21] mostly to inhalant allergens, 19,20 and sometimes the risk is restricted to certain subgroups of the population. 19,20 In contrast, other studies showed no association between BMI BMI from 1 to 7 years for children without asthma at 8 years (solid line) and for children with asthma at 8 years (dashed line) in the BAMSE study.…”
Section: Discussionmentioning
confidence: 99%
“…17 The association between high BMI and allergic sensitization has been less studied, and the results are inconsistent. 8,[17][18][19][20][21] Thus, the association between change in BMI status and timing of overweight in relation to the occurrence of asthma and allergic sensitization merits additional study.…”
mentioning
confidence: 99%
“…Finally, in 1576 Belgian schoolchildren aged between 3.4 and 14.8 years, an increased prevalence of allergic sensitization was found but only in underweight girls, again showing no correlation between weight and allergic respiratory symptoms, eczema or rhino-conjunctivitis. 44 Asthma and obesity: more than a spurious association Although obesity may simply be a marker of lifestyle habits also associated with asthma, several specific mechanisms can be proposed for their association.…”
Section: Introductionmentioning
confidence: 99%